Comparison of symptomatic and asymptomatic persons with primary age-related tauopathy. (17th October 2017) - Besser, Lilah M.; Crary, John F.; Mock, Charles; Kukull, Walter A.
Abstract : Objective: To conduct a clinicopathologic study to characterize clinical and neuropathologic features associated with cognitive impairment in participants with no neuritic amyloid plaques (primary age-related tauopathy [PART] definite) and sparse neuritic plaques (amyloid sparse). Methods: Using the National Alzheimer's Coordinating Center database, we identified 377 individuals who were PART definite (n = 170) or amyloid sparse (n = 207), clinically examined within 1 year of death, and autopsied at 1 of 26 National Institute on Aging–funded Alzheimer's Disease Centers. Factors associated with the odds of being symptomatic (global Clinical Dementia Rating [CDR] score >0) were identified with multivariable logistic regression. Results: PART-definite participants less often had a high Braak neurofibrillary tangle stage V or VI (4%) compared to amyloid sparse participants (28%, p < 0.001). Of the PART-definite participants, 98 were symptomatic and 72 asymptomatic according to their global CDR scores. PART-definite participants were less often symptomatic (58%) compared with amyloid sparse participants (80%, p < 0.001). Within the PART-definite group, independent predictors of symptomatic status included depression (adjusted odds ratio [aOR] 4.20, 95% confidence interval [CI] 2.15–8.19), Braak stage (aOR 1.42, 95% CI 1.04–1.95), and history of stroke (aOR 8.09, 95% CI 2.63–24.82). Within the amyloid sparse group, independent predictors of symptomatic status included education (aOR 0.80, 95% CI 0.65–0.99), Braak stage (aOR 1.91, 95% CI 1.07–3.43), and amyloid angiopathy (aOR 2.75, 95% CI 1.14–6.64). Conclusions: These findings support the hypothesis that participants with PART have an amyloid-independent dementing Alzheimer disease–like temporal lobe tauopathy.